The connection between dysfunctional relationship beliefs and dyadic adjustment - Filipović Severina; Vukosavljević-Gvozden Tatjana; Opačić Goran (Psihološka Istraživanja, 2014)
The purpose of this study was to determine the connection between dyadic adjustment and dysfunctional relationship beliefsthat are discussed in the contemporary cognitive-behavioural perspective. Given the nature of personal relationships, the study included intrapersonal and interpersonal approach. The intrapersonal approach suggests that one's perception of dyadic adjustment is determined by one's own personality characteristics, while the interpersonal approach suggests that one's partner's characteristics have influence, too. Accordingly, it was assumed that people perceive their marriages as less adjusted if they themselves and their partner have more pronounced dysfunctional beliefs. The sample consisted of 100 married couples from Serbia aged 20-64 years (M=41.8). The participants completed the Relationship Beliefs Questionnaire and the Dyadic Adjustment Scale. Significant intrapersonal effects of relationship beliefs on theperceived dyadic adjustment were found for both genders. Expected intrapersonal effects were found only in the female sample. Additionally, unexpected positive effects of certain groups of relationship beliefs(e.g. romantic idealism) were found.